Unpacking Hispanic Ethnicity—Cancer Mortality Differentials Among Hispanic Subgroups in the United States, 2004–2014 - Martinez Tyson, Dinorah; Medina-Ramirez, Patricia; Flores, Ann M.; Siegel, Rebecca; Aguado Loi, Claudia (Frontiers in public health, 2018)
National data on the epidemiology of cancer are commonly reported by broad racial/ethnic categories, such as "Hispanic." However, few studies have disaggregated Hispanic groups and explored mortality differentials in this heterogeneous population. This paper aims to further examine cancer mortality differentials among Hispanic subgroups in the U.S. The study examined cancer deaths in the United States from 2004 to 2014 among decedents classified as Mexican, Puerto Rican, Cuban, Dominican, Central/South American and non-Hispanic white on the death certificate among those who were 20 years or older at the time of death. Data were obtained from the National Vital Statistics System. Sex-specific age-adjusted mortality rates were computed for a 10-year period and each individual year, for all cancers combined. Differences by age group, cancer sites, and age distribution were also assessed. A total of 296,486 Hispanic cancer deaths were identified. Mortality rates of the Hispanic subgroups compare favorably with those of non-Hispanic whites. The mortality rates for Mexicans are very similar to those of all Hispanics combined, whereas the rates for Cuban and Puerto Ricans are higher. Dominicans and Central/South Americans had the overall lowest mortality rates. Statistically significant decreases in cancer mortality rates were noted in some sub-groups, but rates increased among Dominican women. Age-adjusted mortality rates by cancer site varied among Hispanics subgroups and gender. Among Cubans, only 5% of cancer deaths occurred before the age of 50 compared to 16% of cancer deaths among Central/South American. While it is common to present data on the burden of cancer among Hispanics as an aggregate group, this study illustrates that the burden of cancer varies by Hispanic subgroups. The disaggregation of Hispanics by ancestry/country of origin allows for a clearer understanding of the health status of this growing population and is needed if health disparities are to be adequately identified, understood and addressed.